Profit Accountability in Small and Medium Enterprises: An Islamic Accounting Perspective - Husain, Saddan (Universitas Muhammadiyah Makassar, 2025)
This study explores the concept of profit accountability in Small and Medium Enterprises (SMEs) from an Islamic accounting perspective, with a specific focus on SMEs in Bantaeng Regency, South Sulawesi, Indonesia. Recognizing SMEs as vital contributors to regional economic development, this research addresses the limited understanding of how profit is perceived and managed within such enterprises, especially under religious and cultural values. Employing a qualitative field research design, data were collected through interviews, observations, and documentation involving 29 SME actors and local cooperative agencies. Data validity was ensured through triangulation and assessed using the criteria of credibility, transferability, dependability, and confirmability. The findings reveal that SME actors tend to maintain informal and basic financial records. More importantly, the notion of accountability extends beyond human stakeholders to a spiritual accountability to Allah SWT, reflecting the integration of religious values in business practices. Profit, in this context, is not merely financial but also encompasses non-material dimensions such as health, social relationships, knowledge, and spiritual fulfillment. This study contributes to the literature on Islamic accounting by providing a contextual understanding of accountability and profit, offering insights for policymakers and practitioners seeking to support SME development in socio-religious settings.